PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS IV SD NEGERI 67 PEMATANG PUDU KECAMATAN MANDAU KABUPATEN BENGKALIS - Masaleni, Masaleni; Alpusari, Mahmud; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak : This research hield because the law yield from studies result student class IV SDN 67 pematang Pudu Kecamatan Mandau kabupaten Bengkalis. The descrption that studies result IPA student class IV with the average under KKM which decided is 65. This matter can see from student can reach KKM only 11 student 45,8% from 24 student, overwhile students who cant reach KKM scoe amont of 13 student 54,2 % with the total value daily exam 1380 and average is 57,5. This research purpose to increased study resul IPA school year 2015-2016. The research subject are student class IV SDN 67 Pematang Pudu Kecamatan Mandau Kabupaten Bengkalis. The research is the action research class with the two cycle. Research data show that learning process and study result students have progress. It can be prove with the reach score activity teacher on each appointment have increased. One cycle first appointment teacher activity presentation is 75% (good) to 79%(good) on the second appointment and two cycle on the first appointment increased to 87,5%(excellent) and the second appointment increased again to 91,2%(excellent). Students activity on each appointment have grow up, on cycle on the first appointment studies activity is 62,5% (enough) grow up to 70,8% (good) on the second appointment have reach 75% (good) to 83% (excellent). The student study result, this case can see from increased study result from basic score are 11 students person have completed (45,8%) increased to 12 students (50%) on UH I and UH II incresad again to 20 student (83,3%. Therefore can conciluded that hypothesis on this research can applied leaning model cooperative type NHT can increasead study result IPA students class IV SDN 67 Pematang Pudu Kecamatan Mandau kabupaten Bengkalis.Keywords : Numbered Head Together, Learning Outcomes IPA